2023
DOI: 10.3390/genealogy7030048
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Couples’ Discordance on Fertility Desire in Ghana

Abstract: Generally, men in sub-Saharan Africa make reproductive decisions that affect their partners. We examined the predictors of fertility desires among married men across three age cohorts: 20–35 years, 36–50 year, and 51–59 years. Using the 2014 Ghana Demographic and Health Survey dataset, we conducted ANOVA and multivariate binary logistic regressions on 1431 monogamous married men aged 20–59 years. Two indicators of fertility desire are constructed: (i) the comparison of men’s ideal versus women’s ideal family s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In low and middle income countries fertility desired is determined by the husband (7).and male dominance in decision making as far sexual and reproductive health concerned (7-10) which negatively affects women intentions to conceive. Further evidence also showed that discordance in fertility desire among couples (11). Women intentions to conceive is an integral part of reproductive health (RH) right and can be consider as decision making over their fertility.…”
Section: Introductionmentioning
confidence: 99%
“…In low and middle income countries fertility desired is determined by the husband (7).and male dominance in decision making as far sexual and reproductive health concerned (7-10) which negatively affects women intentions to conceive. Further evidence also showed that discordance in fertility desire among couples (11). Women intentions to conceive is an integral part of reproductive health (RH) right and can be consider as decision making over their fertility.…”
Section: Introductionmentioning
confidence: 99%